Planting System Effects on Intercropping of Gardenpea and Sorghum (Bangladesh Agronomy Journal, 2021)
The field experiment was conducted at Agronomy Research Field, Joydebpur and RARS, Burirhat, Rangpur, BARI during Rabi season of 2018-2019 and 2019-2020 to find out suitable combination of sorghum and gardenpea intercropping for higher productivity and monetary advantage. Treatments included in the experiment were: T1 = Sorghum normal row (SNR) + 1 row gardenpea (GP), T2 = SNR + 2 rows GP, T3 = Sorghum paired row (SPR) + 2 rows GP, T4 = SPR + 3 rows GP, T5 = SPR + 4 rows GP, T6 = Sole sorghum (60 cm ´ 10 cm) and T7 = Sole GP (30 cm ´ 10 cm). Light availability on gardenpea decreased with the increase of shade produced by sorghum canopy over the time up to 60 DAS. The lowest light availability on gardenpea was observed in T2 treatment and the highest was observed in sole gardenpea (T7) followed by T3 treatment in both the years. The maximum grain yield of sorghum was observed in T6 and it was decreased (6-10% in 2018-2019 and 1-12% in 2019-2020) at Joydebpur and (5-11% in 2018-2019 and 6-14% in 2019-2020) at Burirhat. The highest sorghum equivalent yield (SEY) of 10.93 t ha-1 in 2018-2019 and 12.02 t ha-1 in 2019-2020 at Joydebpur and 12.06 t ha-1 in 2018-2019 and 11.77 t ha-1 in 2019-2020 at Burirhat and also the highest land equivalent ratio (LER) of 1.77 in 2018-2019 and 1.93 in 2019-2020 at Joydebpur and 1.79 in 2018-2019 and 1.81 in 2019-2020 at Burirhatwere observed in T5 treatment. The highest gross margin of Tk.146600 ha-1 in 2018-2019 and Tk.168400 ha-1 in 2019-2020 at Joydebpur and Tk. 169200 ha-1 in 2018-2019 and Tk.163400 ha-1 in 2019-2020 at Burirhat and also the benefit cost ratio (BCR) of 3.04 in 2018-2019 and 3.34 in 2019-2020 at Joydebpur and 3.35 in 2018-2019 and 3.27 in 2019-2020 at Burirhat were also found in the same treatment. The results revealed that sorghum paired row + 4 rows gardenpea might be agronomically feasible and economically profitable for sorghum + gardenpea intercropping system at Joydebpur and Burirhat region.Bangladesh Agron. J. 2020, 23(2): 59-68